Engagements with Contemporary Literary and Critical Theory - Gottlieb, Evan, 1975- (London : Routledge, 2019)
Engagements with Contemporary Literary and Critical Theory is a wide-ranging but accessible introduction to the key thinkers and theories integral to the study of literature. Organized thematically, the book provides historical introductions and uses a variety of relevant contemporary examples to illuminate the field. Evan Gottlieb contextualizes the latest developments with regard to forms; discourses; subjectivities and embodiments; media, networks, and machines; and animals, affects, objects, and environments. Each chapter elucidates its concepts through in-depth discussions of major contemporary theorists, including Giorgio Agamben, Sara Ahmed, and Catherine Malabou, and uses engaging examples from a canonical novel, a contemporary text, and a new-media artifact to demonstrate theoretical applications. Additional text boxes regularly introduce emerging or overlooked theorists of interest, including Fred Moten and Sianne Ngai. An ideal guide forstudents of literary and criticaltheory, this book will give readers the background they need to continue their own explorations of this vibrant field of study.
Engaging with contemporary literature: Gwyneth Jones's Proof of ConceptEngaging with film and new media: Ryan Coogler's Black Panther; References; 5. Animals, affects, objects, environments; We have never been human; Donna Haraway: cyborgs, companion species, Chthulucene; Sara Ahmed: affects, objects, and feminist killjoys; Timothy Morton: being ecological with object-oriented ontology; Engaging with classic literature: Mary Shelley's Frankenstein; Engaging with contemporary literature: Jeff VanderMeer's Annihilation; Engaging with film and new media: Margaret Atwood's Angel Catbird
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: LITERARY CRITICISM / General; Literature -- History and criticism -- Theory, etc. -- 21st century; Critical theory -- History -- 21st century; Criticism -- History -- 21st century; Literature -- Philosophy -- 21st century